2013
DOI: 10.4187/respcare.02484
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training in Patients With Chronic Respiratory Failure Due to Kyphoscoliosis: A Randomized Controlled Trial

Abstract: BACKGROUND: Research has provided evidence for the safety, feasibility, and efficacy of exercise training in patients with COPD. However, little is known about the impact of exercise training in patients with chronic respiratory failure due to kyphoscoliosis. We evaluated the effect of an exercise training program on exercise capacity, muscle strength, dyspnea, and quality-of-life indices in subjects with chronic respiratory failure due to kyphoscoliosis. METHODS: The 34 subjects were clinically stable, had be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…The authors www.journals.viamedica.pl reported significant decrease in PaCO 2 , while maximum inspiratory and expiratory pressures, as well as endurance time and shuttle walk distance increased significantly. The exercise group had also significantly greater improvements in peripheral muscle strength, dyspnoea, and quality of life [13].…”
Section: Exercise Training and Respiratory Rehabilitationmentioning
confidence: 88%
See 2 more Smart Citations
“…The authors www.journals.viamedica.pl reported significant decrease in PaCO 2 , while maximum inspiratory and expiratory pressures, as well as endurance time and shuttle walk distance increased significantly. The exercise group had also significantly greater improvements in peripheral muscle strength, dyspnoea, and quality of life [13].…”
Section: Exercise Training and Respiratory Rehabilitationmentioning
confidence: 88%
“…Cejudo et al [13] have recommended this kind of exercise programme for the treatment of chronic respiratory failure due to kyphoscoliosis in patients receiving NHMV.…”
Section: Exercise Training and Respiratory Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…29 One potential explanation for the observed difference between the two studies is the duration of the pulmonary rehabilitation program: 4 -6 weeks in our study and 12 weeks in the Cejudo study. 28 In fact, significantly greater improvements in exercise tolerance and dyspnea have been reported in subjects with restrictive lung diseases following a 24-week pulmonary rehabilitation program compared with a 12-week program. 11 In this study, the benefit of pulmonary rehabilitation in terms of improved exercise capacity was completely lost at the 12-month follow-up visit.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of a group of subjects with chronic respiratory failure due to kyphoscoliosis, Cejudo et al 28 reported that exercise training improved exercise capacity, peripheral muscle strength, and HRQOL. The mean 67.2 m increase in shuttle walk distance they reported was far greater than the mean 38 m increase reported by us, despite the similar functional characteristics presented by the two study populations and the significant relationship existing between 6MWD ϭ 6-min walk distance 6MWT ϭ 6-min walk test T0 ϭ at baseline T1 ϭ after rehabilitation T2 ϭ 1 y later the 6MWT and shuttle walk test results.…”
Section: Discussionmentioning
confidence: 99%